2015
DOI: 10.13189/sa.2015.030402
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance Helps to Rural Women for Poverty Reduction in the District of Bogra, Bangladesh

Abstract: The primary objective of this study was to examine the role of microfinance programs in poverty reduction among the poor women in Bogra District. The study was based on data collected from a total of 400 microfinance beneficiaries, which was recruited using a simple random sampling in the year 2011. The study findings suggested that there was no significant relationship of microfinance on specific variables such as household income, education opportunities, employment, health, nutrition, sanitations facilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
2
3
1
Order By: Relevance
“…This upshot is similar to the findings of Rahman (2007), where it has expressed that microcredit has ensured women empowerment. This finding is opposed to the study outcome of Ali et al (2015), which showed microcredit did not empower women, and the social status did not increase after using microcredit.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…This upshot is similar to the findings of Rahman (2007), where it has expressed that microcredit has ensured women empowerment. This finding is opposed to the study outcome of Ali et al (2015), which showed microcredit did not empower women, and the social status did not increase after using microcredit.…”
Section: Discussioncontrasting
confidence: 94%
“…Microfinance institutions also have shown their reluctance in this regard. Similar findings were reported by Hasan (2000), Chowdhury (2009) & Ali et al (2015). These studies found that microfinance is a less effective antipoverty tool to empower women.…”
Section: Microfinance Poverty and Empowermentsupporting
confidence: 87%
“…It is also evident from the survey results that annual household income and per capita income of treatment group were higher than the control group (PKR 331331.56 > PKR 312916.33) and PKR (52687.35 > PKR 47457.27) which further acknowledged the positive role of microfinance on the growth of treatment income. These results are also in lined with some previous studies (e.g., Ali, Islam, & Hatta, 2015: Janjua et al, 2013.…”
Section: Demographic Composition Of Households Profession and Major Sources Of Respondents Incomesupporting
confidence: 94%
“…The development of sustainable finance leads to sustainable social economic and environmental development [51]. The inclusive finance sector is considered an important contributor to the expansion of formal financial systems and has played a significant role in sustainable development [52]. It is playing a leading role to achieve sustainable development by providing access to financial resources and by creating productive opportunities to poor and marginalized people who are usually excluded by conventional banking systems [53,54].…”
Section: Discussionmentioning
confidence: 99%